In this case it is to find the roots of the polynomial.
We have then:
2x ^ 2-5x + 1 = 3
Rewriting:
2x ^ 2-5x-2 = 0
Applying resolver we have
x = (- b +/- root (b ^ 2 - 4ac)) / (2a)
Substituting values:
x = (- (- 5) +/- root ((- 5) ^ 2 - 4 (2) (- 2))) / (2 (2))
x = (- (- 5) +/- root ((25 + 16)) / (2 (2))
x = (5 +/- root (41))) / (4)
x = ((5/4) +/- (root (41)) / 4)
Answer:
x = ((5/4) +/- (root (41)) / 4)
(option 4)
Answer:
I believe you are correct
Hope This Helps! Have A Nice Day!!
Answer:
![\textsf{A)} \quad 5u^3-2u^2+5u+8](https://tex.z-dn.net/?f=%5Ctextsf%7BA%29%7D%20%5Cquad%205u%5E3-2u%5E2%2B5u%2B8)
Step-by-step explanation:
Given expression:
![(-2u^3+5u-1)+(7u^3-2u^2+9)](https://tex.z-dn.net/?f=%28-2u%5E3%2B5u-1%29%2B%287u%5E3-2u%5E2%2B9%29)
Remove parentheses:
![\implies -2u^3+5u-1+7u^3-2u^2+9](https://tex.z-dn.net/?f=%5Cimplies%20-2u%5E3%2B5u-1%2B7u%5E3-2u%5E2%2B9)
Collect like terms:
![\implies -2u^3+7u^3-2u^2+5u-1+9](https://tex.z-dn.net/?f=%5Cimplies%20-2u%5E3%2B7u%5E3-2u%5E2%2B5u-1%2B9)
Combine like terms:
![\implies 5u^3-2u^2+5u+8](https://tex.z-dn.net/?f=%5Cimplies%205u%5E3-2u%5E2%2B5u%2B8)
3y^-4/3 x 2 3/y
Write in exponential form with the base of y
= 3y^-4/3 x 2y^1/3
Calculate the product
= 6y^-1
Any expression raised to the power of equals its reciprocal
= 6 x 1/y
Calculate the product
= 6/y
Answer:
It's D. 53.1°
Step-by-step explanation: